2017
DOI: 10.1017/s2045796017000105
|View full text |Cite
|
Sign up to set email alerts
|

The Singaporean public beliefs about the causes of mental illness: results from a multi-ethnic population-based study

Abstract: Aims. To identify the common causal beliefs of mental illness in a multi-ethnic Southeast Asian community and describe the sociodemographic associations to said beliefs. The factor structure to the causal beliefs scale is explored. The causal beliefs relating to five different mental illnesses (alcohol abuse, depression, obsessive-compulsive disorder (OCD), dementia and schizophrenia) and desire for social distance are also investigated.Methods. Data from 3006 participants from a nationwide vignette-based stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
(73 reference statements)
1
9
0
Order By: Relevance
“…With regard to socio-demographic and diagnostic correlates of caregivers’ causal attributions, those who were economically inactive (students, homemakers, or retired) were less likely to endorse biological attributions compared to those who were employed. A similar result was found in Pang et al.’s (2017) study among the Singapore general population, whereby those who were unemployed (homemaker/student/retired) were less likely to endorse physical factors (i.e., a virus or other infection, an allergy or reaction) compared to those who were employed. It is possible that those who were employed/economically active had more avenues to access information on mental health (e.g., increased socialization, by word-of-mouth, exposure to mental health awareness campaigns) compared to those who were economically inactive, which could have increased their likelihood of endorsing biological causes, given some evidence linking increased mental health literacy with endorsement of these causes (e.g., Bartlett et al., 2006; Jorm et al., 2005; Wang et al., 2013).…”
Section: Discussionsupporting
confidence: 83%
“…With regard to socio-demographic and diagnostic correlates of caregivers’ causal attributions, those who were economically inactive (students, homemakers, or retired) were less likely to endorse biological attributions compared to those who were employed. A similar result was found in Pang et al.’s (2017) study among the Singapore general population, whereby those who were unemployed (homemaker/student/retired) were less likely to endorse physical factors (i.e., a virus or other infection, an allergy or reaction) compared to those who were employed. It is possible that those who were employed/economically active had more avenues to access information on mental health (e.g., increased socialization, by word-of-mouth, exposure to mental health awareness campaigns) compared to those who were economically inactive, which could have increased their likelihood of endorsing biological causes, given some evidence linking increased mental health literacy with endorsement of these causes (e.g., Bartlett et al., 2006; Jorm et al., 2005; Wang et al., 2013).…”
Section: Discussionsupporting
confidence: 83%
“…Compared to persons with AUD, people with other SUDs or with problem gambling behavior were not considerably different with regard to the public attribution of a “bad character” (Hing et al, 2016; Meurk et al, 2014a, 2014b) or moral weakness (DePierre et al, 2014), with the exception of 2018 US study (AUD: 70.3%, SUD: 52.0%; Perry et al, 2020). Pang et al, (2018, Singapore, study #15) conducted a factor analysis with different causal beliefs and identified a “personality” factor determined by high factor loads on the items “weak character” and “being a nervous person.” More than 80% of respondents endorsed causal attribution to this “personality” factor in alcohol abuse.…”
Section: Resultsmentioning
confidence: 99%
“…The model suggests that the more people perceive an individual as having control and responsibility over an negative situation, the less sympathetic they feel toward the individual, which reduces prosocial behavior [27]. A local population-based study on causal beliefs of mental illness found that 89.1% of the participants had attributed personality issues (i.e., being a nervous person or having a weak character) as a cause of depression [29]. With such beliefs, it is likely that the students had perceived depression in their peers as a result of their own personality flaw.…”
Section: Discussionmentioning
confidence: 99%